Online Communication of Local Governments During COVID-19 Pandemic in Hungary - Baranyai, Nóra; Barsi, Boglárka; Nárai, Márta (Frontiers in Political Science, 2021)
Local governments had key and prominent roles in tackling the COVID-19 pandemic. Their task was to take short-term measures quickly and to organize protection and care for those in need. The main objective of our paper is to present how local governments communicated with their inhabitants on various online interfaces in this crisis situation. Our analysis covers 54 settlements representing all the different levels of the settlement network from large cities to small villages. We examined the webpages and Facebook pages of local governments and mayors, first during the first wave and then during the second and third waves of the pandemic. Recognizing their responsibility, local governments clearly tried to provide information to the inhabitants as quickly as possible. They considered the online interfaces the most effective, but the online communication had typically been complemented by information published on more traditional channels as well. There were no significant differences in terms of the way and characteristics of communication among the different types of settlements, although local governments of different sizes obviously had to face different challenges in terms of the amount of tasks they had to tackle. The communication process was a very difficult task because of the lack of information and the not-transparent data provision. Even on the Facebook pages especially suitable for this purpose, interactivity rumbled, and in many cases the questions and suggestions of the inhabitants remained unanswered. It is instructive that, with few exceptions, settlements do not place emphasis on surveying local needs and opinions.